Penerapan Artificial Intelligence dan Machine Learning dalam Sektor Pariwisata Halal: Tinjauan Bibliometrik - Melly Wanda Ismi Wulandari; M. Ruslianor Maika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the development of artificial intelligence (AI) and machine learning (ML) in the halal tourism sector through a review of scientific publications. The researcher used a quantitative method with a bibliometric analysis method to map research trends in this field. This research was conducted by searching the Scopus database using the keywords “artificial intelligence and machine learning in the halal tourism sector” with the categories Article Title, Abstract, and Keywords. The search results were then exported in CSV (Comma Separated Values) format and analyzed using the R-Packages and Biblioshiny Web Interface software applications. The results of the study obtained 465 scientific publications with a time span from 1999 to 2024 using three types of documents, namely articles, books, and conference papers. Bibliometric analysis shows that artificial intelligence has become one of the main drivers of digital transformation in the global tourism sector, including halal tourism. The trend of increasing scientific publications reflects the strategic role of AI and ML in optimizing efficiency, service innovation, and personalization of the traveler experience. The synergy between academic research, technology development, and strategic policy contributes positively to growth in this sector. Overall, the results of this study underline the importance of implementing AI-based technology in meeting the needs of Muslim travelers while strengthening the competitiveness of the halal tourism industry amid rapid global digitization.